Gestión Asociativa Y Eficiencia En El Uso De Recursos De La Producción En El Recinto “El Cuatro” De La Parroquia La Unión, Cantón Babahoyo - 2015. - Muñoz Ponce, Anita Patricia (2015)
This research arises from the reality of the peasant associations Sector Cuatro , which fail to develop an efficient partnership management , enabling them to reap the benefits derived from the partnership, this condition is related to deficiencies in planning productive activities; preventing evaluate the results obtained , the credibility of leaders is variable, not all partners consider to be well directed , individualism and the search for his own benefit is the main factor that has prevented partnering between organizations. The main objective is to present a proposal for strengthening partnership for farmers Sector Associations The Four, trying to improve their performance to achieve success as an organization. A situational analysis through documentary research that shows the attractiveness and necesitad of partnership is made; The first step was the implementation of three instruments, the first instrument applied : Interview with leaders , the second Survey to farmers in the sector; both addressed for information on planning the associative farm management, e- associative control activities and the results of agricultural production, and; the third instrument applied: observation sheet for each of the associations, to determine whether they have all the necessary elements for the development of agricultural activity. The investigation reveals that a partnership with lack of leadership from their leaders and the lack of basic administrative aspects, has not needed to have a successful partnership basis; situation that is evidenced in peasant The Four Sector Associations , whose activities have been neglected by their leaders and partners. In addition, they present disorganization, lack of teamwork, lack of commitment and low sense of belonging; therefore a waste of opportunities associativity. To mitigate this deficiency, this thesis proposes a training plan for the Voluntary Sector Management, to guide the development of joint work in peasant organizations converge Sector Cuatro parish The Union, with an emphasis on organizational strengthening and in the business approach to its activities.